Metode Pembelajaran Mind Mapping dalam Keterampilan Menulis Teks Deskriptif Bahasa Jerman - Anisa, Anisa; Anwar, Muhammad (INSIGHT: Indonesian Journal Social Studies and Humanities, 2025)
Abstract. This research is a Quasi-Experimental research that aims to obtain data and information regarding the effectiveness of the Mind Mapping teaching method on writing skills in German descriptive texts among 11th grade students of SMA Negeri 1 Selayar. The population of this research consisted of 59 students from class XI IPA 4 and XI IPS 3. The sample was selected using a random sampling technique, with class XI IPA 4 as the experimental group (30 students) and class XI IPS 3 as the control group (29 students). The mean score of the experimental class in the pre-test was 61.47, which increased to 87.64 in the post-test. The data were analyzed using t-tests (Paired Samples t-test and Independent Samples t-test). The results of the Paired Samples t-test showed a significance value of 0.000 (< 0.05), and the Independent Samples t-test on the post-test scores of both classes also indicated a significance value of 0.000 (< 0.05). These results demonstrate that the Mind Mapping teaching method is effective in improving students' writing skills in German descriptive texts in class XI of SMA Negeri 1 Selayar Keywords: Mind Mapping, writing skills, text, German language